Odpowiedzi

Najlepsza Odpowiedź!
2010-02-21T15:21:33+01:00
0,2x-3y=1
x-12y=(x+15)/5 +1

0.2x-3y=1
x-12y=(x+15)/6 I6

0,2x-3y=1
6(x-12y) = x+15

0,2x-3y=1
6x-72y=x+15

0,2x-3y=1
6x-x-72y=15

0,2x-3y=1 I(-25)
5x-72y=15

-5x+75y=-25
5x-72y=15
+ _________________
3y= -10 II3
y= 10/3

y=10/3
0,2x-3y=1

y=10/3
0,2x-3*10/3 = 1

y=10/3
0,2x-10=1

y=10/3
0,2x=1+10

y=10/3
0,2x=11 I10

y=10/3
2x=110 II2

y=10/3
x=55

x=55
y=3⅓

Układ oznaczony - ma jedno rozwiązanie.







22 1 22
2010-02-21T15:22:10+01:00
0.2x-3y=1|*(-20)
x-12y=(x+15)/5+1|*5

-4x+60y=-20
5x-60y=x+15+5

5x-4x-x=0

60y-60y=0

15+5-20=0

0=0
odp. ten układ jest nieoznaczony ponieważ nie ma rozwązania
8 4 8